2019
DOI: 10.1021/acs.cgd.8b01660
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Racemic Guaifenesin Applying a Coupled Preferential Crystallization-Selective Dissolution Process: Rational Process Development

Abstract: Preferential crystallization is a cost efficient method to provide pure enantiomers from a racemic mixture of a conglomerate forming system. Exploiting small amounts of pure crystals of both enantiomers, several batch or continuous processes were developed, capable of providing both species. However, an intermediate production step has to be used when pure enantiomers are not available. In such cases, partially selective synthesis, chromatography, or crystallization processes utilizing chiral auxiliaries have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…It is applicable, if the chiral system occurs as conglomerate-i.e., if the enantiomers crystallize as separate enantiopure crystals [3,4]. Continuous processes for preferential crystallization have been suggested in [5][6][7]. A simple process variant is shown in Figure 1.…”
Section: Continuous Enantioseparation By Preferential Crystallizationmentioning
confidence: 99%
See 3 more Smart Citations
“…It is applicable, if the chiral system occurs as conglomerate-i.e., if the enantiomers crystallize as separate enantiopure crystals [3,4]. Continuous processes for preferential crystallization have been suggested in [5][6][7]. A simple process variant is shown in Figure 1.…”
Section: Continuous Enantioseparation By Preferential Crystallizationmentioning
confidence: 99%
“…The number size densities in the red and blue regions in the right-hand side diagram at time T min are just copies of the number size densities at time t = 0 in the left-hand side diagram. The number size densities in the white unshaded area of the right-hand side diagram depend on nucleation and can be determined with Equation (6).…”
Section: Solution Of the Linear Model By Stepping Forward In Time Witmentioning
confidence: 99%
See 2 more Smart Citations
“…Phase diagrams are important tools for understanding and controlling crystallization. Indeed, the construction of a phase diagram is essential for rationally 1) determining the appropriate crystallization conditions for molecules exhibiting multiple solid phases, 2) assessing the thermodynamic stability of solid phases, and 3) controlling the supersaturation . Recently, our group demonstrated that PC could be applied to a metastable conglomerate of diprophylline, which crystallizes in multiple crystal forms depending on the conditions .…”
Section: Introductionmentioning
confidence: 99%